Comparison of Polyethylene Oxide and Polyvinyl Alcohol as a Host for Graphene Saturable Absorber at 1.5 µm Region (ELEKTRIKA- Journal of Electrical Engineering, 2023)
This paper compares the performance of two polymeric substance, polyvinyl alcohol (PVA) and polyethylene oxide (PEO) as a host in graphene saturable absorber (SA) fabrication. By applying a low-cost solution casting method, graphene flakes which was prepared using the electro-chemical exfoliation technique will be mixed with PEO or PVA solvent as a host. Single concentration (12.04 wt.%) of graphene-PVA and graphene-PEO has been prepared for comparison. At 1.5 µm wavelength region, 2.8 meters erbium doped fiber (EDF) was applied as a gain medium in ring laser cavity setup. Generally, our measurement confirmed stable Q-switched pulses generation (>30 dB) for both SAs at 1.5 µm region. Evidently, the generated pulse by graphene-PVA at 1531.1 nm produced shorter pulse width of 1.85 µs as compared to 18.1 µs by graphene-PEO at maximum permissible pump power. Although smaller pulse energy was calculated for graphene-PVA, the ability of this type of SA to withstand higher pump-power proved its superiority as compared to its counterpart. Notably, this is the first ever effort that assess the performance of PVA and PEO host in graphene-based saturable absorption, particularly at 1.5 µm region.